2021
DOI: 10.1093/intqhc/mzab018
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the impact of delayed access to elective cholecystectomy through patient’s cost-utility: an observational cohort study

Abstract: Background Deferral of surgeries due to COVID-19 has negatively affected access to elective surgery and may have deleterious consequences for patient’s health. Delays in access to elective surgery are not uniform in their impact on patients with different attributes. The objective of this study is to measure the change in patient’s cost utility due to delayed elective cholecystectomy. Methods This study is based on retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
1
6
0
1
Order By: Relevance
“… 89 According to a study in the UK, 3 to 6 months delay in cancer surgeries could have terrible effects on life‐years gained (LYG's) from cancer surgery which would cause the attributable death of 4755 out of 10 760 cases. 90 , 91 (Figure 3 ).…”
Section: Methodsmentioning
confidence: 99%
“… 89 According to a study in the UK, 3 to 6 months delay in cancer surgeries could have terrible effects on life‐years gained (LYG's) from cancer surgery which would cause the attributable death of 4755 out of 10 760 cases. 90 , 91 (Figure 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…Across Canada, there has been decreased care-seeking and system-wide redistribution of resources during the COVID-19 pandemic, leading to reduced treatment across diverse areas of medicine ( 2 , 5 , 6 ). As the first Canadian study in hepatology patients, we found that 38% of outpatients with chronic liver disease reported care delays, the majority of which were on the scale of months.…”
Section: Discussionmentioning
confidence: 99%
“…O presente estudo apresentou uma amostra quantitativamente pequena, devido redução do volume cirúrgico institucional de cirurgias eletivas não oncológicas após impacto pela pandemia de Coronavírus Sars-CoV-2, também evidenciado em outros centros 20,21 .…”
Section: Discussionunclassified